The effect of hydrocarbon exposure and temperature on the behaviour of elastomeric seals - Scully, Christopher (Department of Chemical Engineering, 2016)
Synthetic jet fuels have been proposed as alternatives to petroleum Jet A-1. Compatibility issues, however, are of concern; specifically the interaction of synthetic fuels with polymeric materials which are commonly used to seal fuel systems. This is because of differences between the composition of synthetic fuels and petroleum-derived fuels. Synthetic fuel streams contain no or very low aromatics, unlike petroleum-derived fuels. This investigation was consequently initiated to gain a greater understanding of the factors affecting seal swell in the aviation industry. The study focussed interactions between fuel components from various fuel classes and nitrile rubber (NBR) as well as a restricted set of investigations on fluorocarbon (FKM) rubber. No comprehensive study of the temperature sensitivity of fuel composition on swelling has been attempted prior to this study. NBR and FKM were swollen in petroleum Jet A-1, synthesised paraffinic kerosene (SPK) and a variety of blends of pure components with SPK. These components were selected from aromatic species (monoaromatic, diaromatic and heterocyclic), cycloparaffins, aromatic oxygenates and other oxygenates. Aromatic species were blended at 8% (v/v) while all other species were blended at 15% (v/v). Within the class of aromatic hydrocarbon components, it was found that decreasing molecular size, increasing the number of ring structures (particular aromatic rings) as well as increasing all Hansen solubility parameters increased swelling. Of the Hansen solubility parameters, the greatest correlation was found with the hydrogen-bonding (electron exchange) parameter. Nonetheless the dispersion parameter which is strongly affected by the number of aromatic rings and length of any aliphatic side-chain was also important. A very good correlation was found between swelling and the density of the aromatic species. It was found furthermore that introducing oxygen atoms increased swelling. The introduction of cycloparaffins also increase swelling although to a much lesser extent than aromatics. Cyclisation together with a polar moiety was observed to increase swell significantly. With FKM elastomers, fuel composition had less influence. Temperature sensitivity was explored by performing swelling at 20oC, 35 oC and 50 oC. Van't Hoff plots were used to obtain enthalpies of mixing. It was found that all hydrocarbons swelled more as temperature rose. This is indicative of endothermic interactions between these species and polar NBR. However, it was observed that species with high polar and hydrogenbonding Hansen solubility parameters had lower sensitivity to temperature. It is postulated that in these species, less aromatic concentration in the NBR occurs at elevated temperatures, contributing to lower sensitivities. Aromatic oxygenates were observed to decrease in swelling with temperature. This is ascribed to a strong exothermic interaction. This behaviour was in contrast to non-aromatic oxygenates. It is possible that blends of these non-aromatic oxygenates with SPK are less stable at elevated temperatures leading to component separation into the NBR and thus more swelling. Similar trends were observed with fluorocarbon elastomers (FKM). Physical property measurements were made on swollen NBR O-rings. A distinct relationship between decreased glass transition temperature and the extent of swelling was observed. Fuel which had adsorbed into the elastomer was observed to act as an effective plasticiser. Not only did increased swelling lower the glass transition temperature but it reduced the modulus of NBR O-rings in a predictable fashion. A significant decrease in storage modulus was associated with increased swelling. Increased swelling was found to be associated with increased compression set although the mechanism by which this manifests itself is unclear.